The relationship between the feedback environment and creativity: a self-motives perspective - Gong Z; Shan C; Yu H (Psychology Research and Behavior Management, 2019)
Zhenxing Gong,1 Chao Shan,1 Haizhen Yu2 1Department of Business Administration, School of Business, Liaocheng University, Liaocheng 252000, People’s Republic of China; 2Technical Reconnaissance Department, Liaocheng Public Security Bureau, Liaocheng 252000, People’s Republic of ChinaCorrespondence: Zhenxing GongDepartment of Business Administration, School of Business, Liaocheng University, No. 1 Hunan Road, Dongchangfu District, Liaocheng 252000, People’s Republic of ChinaTel +86 1 890 635 0166Email zxgong118@163.comBackground: For companies, employee creativity is vital to gaining competitive business advantages. Research regarding creativity has focused on contextual factors such as feedback, but results of studies on the relationship between feedback and creativity are inconsistent; further, only a handful of studies have been carried out from the perspective of coworkers. In this study, we aimed to analyze the association between the coworker feedback environment and creativity, to test the mediating role of feedback monitoring in this relationship and to test the moderating role of self-motivation among employees in China.Methods: A coworker feedback environment survey, a coworker feedback monitoring questionnaire, a self-motivation scale and a creativity scale were used. The staff submitted 264 questionnaires, of which 235 (74.6%) were completed by the participants. Among the respondents in the sample, 132 (56.2%) were men, and 103 (43.8%) were women. The mean age is 30 and age range from 24–49. Mplus 7.11 software was used to perform descriptive analysis, Spearman’s correlation analysis, mediating analysis and moderation analysis.Results: Coworker feedback environment was positively associated with creativity (β=0.60, p<0.01) after controlling for the demographic variable. Coworker feedback monitoring partially mediated the relationship between coworker feedback environment and creativity (χ2/df=2.5, RMSEA=0.05; CFI=0.93; GFI=0.93). When self-assessment motivation is lower, the positive relationship between coworker feedback monitoring and creativity becomes stronger (β=0.19); the same relationship becomes weaker (β=0.01) when self-assessment motivation is higher.Conclusion: It was suggested that a coworker feedback environment could improve employee creativity by promoting coworker feedback monitoring; creativity could be improved especially among employees who have lower self-assessment motivation.Keywords: feedback environment, creativity, feedback seeking, self-motivation